DIFFERENCES IN JUVENILE DELINQUENCY CAUSED BY FATHER ABSENCE - Sekar Arum Sabrina; Dewi Retno Suminar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to discover whether there are differences in juvenile delinquency due to father absence. The absence covered in this study comprises the father’s death, parental divorce, and the demands to work away from home. This study was performed to 12-21 years old adolescents who do not live together with their father. The measuring instrument used in this study was the inclination scale of juvenile delinquency on the theory of planned behavior by Fishbein and Ajzen. The data were quantitatively analyzed by using the Kruskal-Wallis. The results of the analysis showed the significance level of 0.012<0.05, implying that there is an inclination of juvenile delinquency among the subjects with father’s death, parental divorce, and fathers working away from home. In brief, it can be concluded that there is a significant difference noticed in the three groups of father absence. Moreover, the level of delinquency in male adolescents is higher than in female adolescents